The building blocks of an effective performance management system: A comprehensive review - Rahmita, Silvia; Fahmy, Rahmi; Syahrul, Laura (Nur Science Institute, 2025)
An effective performance management system (PMS) needs special recognition from researchers, specifically regarding its holistic and comprehensive approach to improving organizational effectiveness. Researchers' interest in the effectiveness of PMS is relatively high from various perspectives. This study aims to determine which antecedents drive effective PMS comprehensively. This research was conducted using a systematic literature review of research articles from 2000 to the latest in 2024. The review included 28 final articles from reputable journals. Several critical elements of effective PMS were discovered: regular feedback and effective communication, employee involvement and empowerment, fairness and objectivity, strategic alignment and integration, clear performance goals and planning, top management commitment, performance-oriented culture, integrating PMS, and rewards and recognition. By focusing on these aspects, organizations can ensure that their employees are engaged and motivated, supporting their strategic goals.